Understanding the Rudhita Synonyms of Plants as Scientific Information - Kamble, Sharavati Goroba (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is the science of life in which all the details related to health and illness are explained in three categories viz. Hetu - causative factors, Linga - signs and symptoms and Aushadha - medicine. Further, Aushadha is explained in detail as treatment or procedure. Plants are one of the major constituents of the treatment part. In various Ayurvedic Samhitas, plants were described in brief until specific Granthas or texts were written focusing the plants. The texts in which the data about plants is compiled and recorded are classified as Nighantu. In Nighantu the information about plants is divided into two parts, synonyms and properties. Synonyms are considered as the guide for the identification of the plant in particular. This article aims to unravel the mysterious yet scientific information held by the synonym of certain plants. Some plants have synonyms based on Rudhi (Tradition) or Tale. To understand the Rudhita synonyms in detail, four plants viz. Shami, Agasti, Bilva and Kutaja are selected and reviewed for their literary meaning and properties. It is observed that the synonyms of these plants like Agnigarbha for Prosopis cineraria (Shami), Agasti for Sesbania grandiflora (Hadga), Bilva, Shreephala for Aegle marmelos (Bael) and Indravruksha for Holarrhena antidysenterica (Kutaja) hold specific properties and different scientific information than mere names.